Derivatives of 3:4-xylidine and related compounds as inhibitors of influenza virus: relationships between chemical structure and biological activity - Clark, R. J. (1958)
A series of compounds, based primarily on 3:4-xylidine, was examined for inhibitory activity towards the growth of influenza virus in tissue culture. Marked dependence of inhibitory activity upon chemical structure was observed particularly when the 3:4-xylyl group was replaced by other simple aryl radicals. N-(2-Piperidinoethyl)-3:4-xylidine dihydrochloride, a typical compound combining high intrinsic inhibitory activity with no obvious toxicity towards the host tissues, did not inactivate the virus directly before its adsorption, did not interfere with adsorption of virus by the tissues, and did not inhibit the release of freshly synthesized virus by the tissues, but specifically depressed the synthesis of viral haemagglutinin to a greater extent than it depressed the synthesis of complement-fixing soluble antigen. The inhibition of growth of influenza virus caused by this compound in tissue culture was reversed by appropriate addition of 4:5-dimethyl-o-phenylenediamine, but not apparently by riboflavin or by vitamin B(12). The action of this substance, and, by inference, of related compounds, in inhibiting viral synthesis may be the result of depressed cytoplasmic protein synthesis.